Physical Abuse Perpetrated by In-laws: An Analysis of Nationally Representative Survey Data from 47 Low- and Middle-income Countries - Waila, Jacinta Mukulu; Wilson, Michael Lowery; Bärnighausen, Till; Abio, Anne (SPRINGER/PLENUM PUBLISHERS, 2025)
Purpose
Violence within extended kinship contexts remains understudied. This study sought to estimate the prevalence of physical violence perpetrated by in-laws.
Methods
Demographic and Health Surveys’ data collected between 2011 and 2020 were utilized. Data for females and males were derived from 47 and 10 countries respectively. We estimated the prevalence of being physically hurt by mothers-in-law, fathers-in-law and other in-laws against participating females (n=420 020) and males (n=71 629) separately.
Results
The pooled prevalence for in-law perpetrated physical violence against female respondents was 0.38% (95% CI 0.34, 0.42). The prevalence of violence from mothers-in-law was 0.18% (95% CI 0.15, 0.21), fathers-in-law was 0.11% (95% CI 0.09, 0.13) and other in-laws 0.20% (95% CI 0.17, 0.23). The pooled prevalence of in-law violence against male respondents was 0.56%; (95% CI 0.45, 0.71), and from mothers-in-law was 0.08%; (95% CI 0.05, 0.13), fathers-in-law was 0.05%; (95% CI 0.03, 0.09) and other in-laws was 0.51%; (95% CI 0.39, 0.66). Among individual countries, the highest prevalence among females and males was recorded in Afghanistan at 4.07% (95% CI 3.30, 5.02) and in Mozambique at 2.24%; (95% CI 1.56, 3.20) respectively.
Conclusion
Violence by in-laws affects both men and women in varying degrees across different countries. The data indicate that it is possible for one individual to experience violence perpetrated by more than one extended family member. Given the paucity of research in this area, it is hoped that the results may stimulate further inquiry into relevant contextual and social variables which influence in-law violence.